Operação de Wertheim-Meigs em carcinoma do colo do útero e tratamento complementar: análise crítica de cinco anos. - Freitas, Daniela; Rodrigues, Fedra; Fernandes, Daniel; Petiz, Almerinda (Acta Médica Portuguesa, 2011)
Review and critical analysis of the Wertheim-Meigs Operations performed at our institution in the context of cervical cancer and to assess the proportion who underwent treatment with adjuvant radiotherapy (with or without chemotherapy) and the main indications.Retrospective review of Wertheim-Meigs operations, conducted in the context of carcinoma of the cervix, between 01.01.2005 and 31.12.2010, through consultation with clinical processes. It was later performed a descriptive statistical analysis of the cases.During this period 119 Wertheim-Meigs Operations were performed. Four were excluded: two, for primary indication for adjuvant therapy due to histological subtype; two for the inability to exclude invasive disease preoperatively and the invasion was not confirmed after surgery. A total of 115 cases were reviewed and analyzed, and of these 50 (43.5%) underwent complementary therapy, the main indication being the presence of lymphovascular invasion in 21 cases (42% of cases submitted to complementary therapy ).The mean age of patients undergoing radical surgery is 49 years, with stage IB1 most often determining its performance. Complementary therapy was performed in 43.5% of cases, the main indication being lymphovascular invasion (42%) followed by lymph node invasion (16%). Internal audit to the Service is satisfactory, with 16.5% surgical complication rate and high technical performance.